Rekonstruksi Kedudukan Epistemologis Tabi'in dan Ijtihad dalam Hierarki Sumber Tafsir: Model Integrasi dalam Qawā'id Al-Tafsīr - Nurul Hidayah Baharuddin; Andi Miswar; Hamka Ilyas (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Studies on the opinions of the Tābi'īn and ijtihād as sources of Qur'anic interpretation have generally been discussed separately, with limited attention to their epistemological relationship within the framework of qawā'id al-tafsīr as a methodological basis for evaluating contemporary Qur'anic exegesis. This study aims to reconstruct the epistemological position of the opinions of the Tābi'īn and ijtihād in the hierarchy of interpretive sources and to formulate an integrative conceptual model that explains their relationship in the development of contemporary Qur'anic interpretation. This research employs a qualitative library research approach by examining classical works of Qur'anic exegesis and Qur'anic sciences, including Jāmi' al-Bayān by al-Ṭabarī, Tafsīr al-Qur'ān al-'Aẓīm by Ibn Kathīr, al-Burhān fī 'Ulūm al-Qur'ān by al-Zarkashī, and al-Itqān fī 'Ulūm al-Qur'ān by al-Suyūṭī, which are analyzed comparatively alongside the perspectives of contemporary Muslim scholars. The findings demonstrate that the authority of the opinions of the Tābi'īn is not absolute but is determined by the authenticity of the transmitted reports, the reliability of their chains of transmission, and their conformity with the established principles of qawā'id al-tafsīr. Likewise, ijtihād is recognized as a legitimate source of interpretation only when it adheres to the methodological principles governing Qur'anic exegesis rather than representing unrestricted interpretive freedom. This study proposes an integrative epistemological model positioning the opinions of the Tābi'īn as the authoritative transmitted foundation (naql) and ijtihād as the methodological instrument for contextualizing Qur'anic meanings in response to contemporary issues. This model contributes theoretically to strengthening the methodological framework of Qur'anic interpretation and provides an evaluative basis for assessing the validity of contemporary exegetical approaches.